LANCAR MENGAJI DAN HAFAL AL-QURAN BERSAMA MAHASISWA KKN UNP DI JORONG BATUANG, KURAI - Riza Umami; Edi Saputra; Rahma Nadila Putri; Saharani Yarietsa; Widia Eka Putri; Mei Syarah Anis; Rezi Asria Nanda; Tiara Khairatunisa; Mustafa Syendy Assidiq; Figo Armando Sufli (Bajang Institute, 2023)
Real Work Lecture (KKN) is an intra-curricular activity that combines the implementation of the Tri Dharma of Higher Education with methods of providing learning and work experience to students in community empowerment activities. The main work program carried out during the KKN is teaching tahfidz and also tutoring for the children of Nagari Kurai. These activities are carried out to fill the children's vacation time more useful. The tahfidz teaching program is carried out with the aim of increasing Al-Qur'an recitation and increasing memorization of Al-Qur'an verses for children. While tutoring is carried out with the aim of recalling past learning material and adding new knowledge to the children in Nagari Kurai. Apart from these two work programs, there are also several work programs carried out by KKN UNP students in Nagari Kurai such as mutual cooperation, nature walks, and so on. Community Service Program activities last for one month starting from June 19 2023 to July 19 2023